Band Structure Engineering of Schiff‐Base Microporous Organic Polymers for Enhanced Visible‐Light Photocatalytic Performance. Issue 34 (1st July 2019) - Xiao, Zhichang; Huang, Xiaoxiong; Zhao, Kun; Song, Qi; Guo, Ruiying; Zhang, Xinghao; Zhou, Shanke; Kong, Debin; Wagner, Manfred; Müllen, Klaus; Zhi, Linjie
Abstract: Schiff‐base networks (SBNs), as typical examples of nitrogen‐doped microporous organic polymers (MOPs), exhibit promising application prospects owing to their stable properties and tunable chemical structures. However, their band structure engineering, which plays a key role in optical properties, remains elusive due to the complicated mechanisms behind energy level adjustment. In this work, a series of SBNs are fabricated by tailoring the ratio of p‐phthalaldehyde and o‐phthalaldehyde in the Schiff‐base chemistry reaction with melamine, resulting in a straightforward as well as continuous tuning of their band gaps ranging from 4.4 to 1.4 eV. Consequently, SBNs can be successfully used as photocatalysts with excellent visible‐light photocatalytic activity even under metal‐free conditions. Significantly, electronic structures of SBNs are systematically studied by electrochemical and spectroscopic characterizations, demonstrating that the enhanced performance is ascribed to proper band structure and improved charge separation ability. More importantly, in combination with theoretical calculations, the band structure regulation mechanism and band structure‐photocatalytic property relationship are deeply disclosed. The results obtained from this study will not only furnish SBN materials with excellent performance for solar energy conversion, but also open up elegant protocols for the molecular engineering of MOPs with desirable band structures. Abstract : A novel class of Schiff‐base microporous networks is synthesized with variable band structure in a wide and continuous range, and the mechanism of band structure engineering is investigated both theoretically and experimentally. With optimized chemical structures, excellent photocatalytic activity even in metal‐free conditions under visible light can be achieved.